RESTRUKTURISASI SEBAGAI UPAYA PENYELAMATAN BANK KEPADA DEBITUR YANG TERDAMPAK COVID 19 - robiah zakiah; Septiana Restu Wulandari; ahmad munandam (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2021)
The Covid 19 pandemic not only has an impact on the healty sector, but has a major impact on the Indonesia economic sektor. The development and spread of the Covid-19 virus is directly or indirectly affected by bank performance and financila sistem stability in a country. The impact ofe the Covid- 19 Pandemic on the banking sector is different for each segment. Banking is all aspects related to bank institutions, while banks are all aspects related to financial. The problem related by banks is that the performance and capacity of debtions to pas credit has been disrupted by the spread of Covid-19, thus disrupting bank and credit performanc. Therefore optimizing the function of bank to maintain financial system stability and stimulate the economy. Indonesia is need of a policy to overcome the effects of the spread of Covid-19. The policy issued by Financila Services Authority (OJK) regarding the provision of restrukturisasi for debtors affected by Covid-19 pandemic. One of the stimulus to boost the economy in Indonesia namely the grating of leewar or relaxation of micro, small and medium-sixed loans (UMKM). The requirwmwnt for applying for restructurisasi to bank are difficulties in paying principal and/or interest on loans and the debitur has good business potential and is considered capable of fulfilling his obligations.